Deep vein thrombosis as a rare complication of scrub typhus - Arun Kumar Alagesan; R., Kannan; V., Vikrannth; J., Raghav (International Journal of Advances in Medicine, 2023)
Scrub typhus is a common re-emerging, acute febrile infectious disease, caused by orientia tsutsugamushi, transmitted by bite of chiggers of trombiculid mite. The clinical presentation of infection can vary from mild symptoms to severe multi organ failure, shock, encephalopathy, meningoencephalitis, DIC and various thromboembolic complications. We describe a rare hematological complication of deep vein thrombosis (DVT) caused by scrub typhus in a 61-year-old female. Vasculitis and perivasculitis with endothelial dysfunction could be considered as the main pathologic mechanism causing this complication.